2023
DOI: 10.1080/15592324.2023.2287881
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic pathways and related genes regulation of bioactive ingredients in mulberry leaves

Na Lu,
Lei Zhang,
Yuqing Tian
et al.

Abstract: Mulberry leaves are served not only as fodder for silkworms but also as potential functional food, exhibiting nutritional and medical benefits due to the complex and diverse constituents, including alkaloids, flavonoids, phenolic acids, and benzofurans, which possess a wide range of biological activities, such as anti-diabete, anti-oxidant, anti-inflammatory, and so on. Nevertheless, compared with the well-studied phytochemistry and pharmacology of mulberry leaves, the current understanding of the biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…These compounds are also shown to inhibit pathways related to metabolic disorders like insulin resistance and improper cell function. Specific microbial communities, such as Bacteroidetes and Firmicutes, play a crucial role in energy metabolism and cellular physiological functions [148,166]. Ongoing research has revealed that certain mulberry compounds like flavonoids, polysaccharides, alkaloids, and phenolic acids can enhance gut microbiota diversity in animal models with certain metabolic disorders, as shown in Table 3.…”
Section: Anti-inflammatory Effect Of Mulberry Through Regulation Of G...mentioning
confidence: 99%
“…These compounds are also shown to inhibit pathways related to metabolic disorders like insulin resistance and improper cell function. Specific microbial communities, such as Bacteroidetes and Firmicutes, play a crucial role in energy metabolism and cellular physiological functions [148,166]. Ongoing research has revealed that certain mulberry compounds like flavonoids, polysaccharides, alkaloids, and phenolic acids can enhance gut microbiota diversity in animal models with certain metabolic disorders, as shown in Table 3.…”
Section: Anti-inflammatory Effect Of Mulberry Through Regulation Of G...mentioning
confidence: 99%